Self-Assembling Polyhedral Silsesquioxanes - Structure and Properties - Kowalewska, Anna (Current Organic Chemistry, 2017)
Polyhedral oligomeric silsesquioxanes (POSS) are perfect three-dimensional elemental building blocks that can be used for construction of diverse inorganic/organic hybrid materials. Well-defined inorganic frameworks, tailor-made physicochemical properties and symmetric distribution of organic groups make the hybrid organo-silica compounds ideal nano-fillers for polymer composites. Understanding the phenomena directing the molecular packing morphology of neat polyhedral silsesquioxanes is very important for an effective control of hierarchal structures and physicochemical properties of POSS-based hybrid materials, especially for the adjustment of polymer-nanoparticle interfacial interactions. The segmental dynamics of POSS derivatives in hybrid nanomaterials can be strongly influenced by their structural features. The review presents an analysis of intrinsic self-assembly behaviour of polyhedral silsesquioxanes and their derivatives including capability of the formation of more complex hierarchical superstructures in solid state. The stability of the formed self-assembled structures was analyzed with special regard to thermally induced solid-solid state phase transitions. The role of hierarchical structures present in a range of POSSbased advanced materials, including amphiphilic macromolecules, nanoparticles and liquid crystals is discussed.
Keywords: solid-state interactions